Hubungan Senam Lansia pada Tekanan Darah dan Gula Darah Lansia Desa Kalitengah Blitar - Mohammad Ghibran Maldini (Pusat riset dan Inovasi Nasional, 2024)
This study was motivated by the high prevalence of high blood pressure (hypertension) and uncontrolled blood sugar levels among the elderly, particularly in Kalitengah Village, Blitar Regency. The elderly are a vulnerable group to health problems due to a decline in physiological function, which can lead to serious complications such as stroke, heart failure, and diabetes mellitus. This study aims to determine the relationship between elderly exercise activities and blood pressure and blood sugar levels. The method used is quantitative with a correlational design. The study subjects consisted of 30 elderly individuals who actively participated in regular exercise activities at the Kalitengah Village Health Post. Measurements were taken of systolic and diastolic blood pressure and blood sugar levels before and after the exercise intervention. Based on the findings supported by previous literature reviews, it is known that physical activities such as elderly exercise significantly reduce blood pressure and help control blood sugar levels. The findings of this study indicate that regular exercise can improve blood pressure and blood glucose parameters. The results of this study are expected to serve as a basis for promotive and preventive efforts to improve the quality of life of the elderly through community-based interventions that are easy, affordable, and effective, namely elderly exercise.